Governmental activity, integration, and agglomeration - Ingrid Ott; Susanne Soretz (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2007)
This paper analyzes, within a regional growth model, the impact of productive governmental policy and integration on the spatial distribution of economic activity. Integration is understood as enhancing territorial cooperation between the regions, and it describes the extent to which one region may benefit from the other region's public input, e.g. the extent to which regional road networks are connected. Both integration and the characteristics of the public input crucially affect whether agglomeration arises and if so to which extent economic activity is concentrated: As a consequence of enhanced integration, agglomeration is less likely to arise and concentration will be lower. Relative congestion reinforces agglomeration, thereby increasing equilibrium concentration. Due to the congestion externalities, the market outcome ends up in suboptimally high concentration.
Keywords: O4; R5; 330; public inputs; agglomeration; integration